2007
DOI: 10.1111/j.1748-5827.2007.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoid sinus and bone defects of the fifth thoracic vertebrae in a shih‐tzu

Abstract: LETTERSDermoid sinus and bone defects of the fifth thoracic vertebrae in a shih-tzu MADAMRecently, we encountered a five year old, neutered, male shihtzu presented with an acute onset of ataxia of the pelvic limbs after a tuft of hair, protruding from a dermoid sinus on the dorsal midline of the cranial thoracic region, had been pulled by the groomer. Radiographs showed a defect of the spinous process and the vertebral bodyof T5. The spinous process was found to be separated into two sections forming an openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 1 publication
2
16
0
1
Order By: Relevance
“…In rare cases, a dermoid sinus can be associated with vertebral malformations, as in these cases presented here (Selcer and others 1984, Fatone and others 1995, Cornegliani and others 2001, Bowens and others 2005, Colon and others 2007, Tong and Simpson 2009). Spina bifida seems to be related to dermoid sinuses that reach the spinal canal (Fatone and others 1995, Pratt and others 2000, Bowens and others 2005, Colon and others 2007, Tong and Simpson 2009). This may be due to the interaction between neural crest, mesoderm (the embryological origin of the bone tissue) and the neuroectodermal neural tube that is required for normal development of the neuraxis.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In rare cases, a dermoid sinus can be associated with vertebral malformations, as in these cases presented here (Selcer and others 1984, Fatone and others 1995, Cornegliani and others 2001, Bowens and others 2005, Colon and others 2007, Tong and Simpson 2009). Spina bifida seems to be related to dermoid sinuses that reach the spinal canal (Fatone and others 1995, Pratt and others 2000, Bowens and others 2005, Colon and others 2007, Tong and Simpson 2009). This may be due to the interaction between neural crest, mesoderm (the embryological origin of the bone tissue) and the neuroectodermal neural tube that is required for normal development of the neuraxis.…”
Section: Discussionsupporting
confidence: 58%
“…Dermoid sinuses can, however, be asymptomatic for months to years before becoming infected or inflamed (Selcer and others 1984, Marks and others 1993, Lambrechts 1996, Pratt and others 2000, Davies and others 2004) or can cause spinal cord compression due to debris accumulation (Fatone and others 1995) or cyst enlargement (Tong and Simpson 2009). Neurological abnormalities can also occur acutely because of trauma caused by pulling the protruding hair from the sinus in asymptomatic animals (Colon and others 2007). These facts support the idea of preventive surgery at least in cases where the defects extend to the spinal canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their characteristic cutaneous ridge in this breed is an autosomal dominant mutation of fibroblast growth factor genes that predispose the animals to dermoid sinus [39,40]. This developmental abnormality has been reported in several other breeds, including the American Cocker Spaniel, English Cocker Spaniel, English Springer Spaniel, Boxer, Chow-Chow, Golden Retriever, Shih Tzu, Siberian Husky, Yorkshire Terrier, German Shepherd, Rottweiler, Boerboel, Great Pyrenees, Swedish Vallhund, Chinese Crested, Victorian Bulldog, and occasionally in domestic cats [6-8,11-14,16,17,41-46]. No reports of dermoid sinus in Dachshunds were found in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…Isolated cases of DS have also been reported in other breeds (Table 1) [9-40], without evidence of a genetic predisposition [34,51]. Several authors have reported that DSes are found most frequently in the cervical and thoracic regions [11,14,38] with possible extension to the meninges and subarachnoid space [9,21,23,32,33,35-37,39,40]. They are less frequently found in the sacral region [38].…”
Section: Introductionmentioning
confidence: 99%